Managing Infographic-Mediated Indonesian Language Instruction to Improve Elementary Students' Procedural Writing Skills - Sisca Rachmawati; Nana Herdiana Abdurrahman (Papanda Publisher, 2026)
Elementary students frequently encounter challenges in developing writing proficiency due to inadequate instructional strategies and limited engagement with conventional text-based approaches. This study examined the management of Indonesian language instruction incorporating infographic media to enhance elementary students' procedural writing skills through systematic PDCA (Plan-Do-Check-Act) cycle implementation. A qualitative multiple case study was conducted at two elementary schools (SDN Sindanglaya and SDN Panagan) in Cianjur Regency, Indonesia. Data were collected through classroom observations (24 sessions), semi-structured interviews with teachers (n=4), principals (n=2), and students (n=48), and document analysis of instructional artifacts. Data analysis followed Miles et al.'s systematic procedures encompassing data reduction, display, and conclusion drawing with cross-case comparison. Findings revealed that structured infographic-based instructional management significantly improved students' writing quality (34% average improvement) with particularly substantial gains in structural organization (47%). Student engagement during infographic activities (78%) substantially exceeded traditional instruction (52%). Teachers demonstrated pedagogical adaptability despite technological constraints, while systematic evaluation and continuous improvement processes enhanced instructional effectiveness. PDCA-based management of infographic-mediated instruction represents an effective, evidence-based approach for enhancing elementary writing instruction when implemented through comprehensive frameworks encompassing rigorous planning, adaptive pedagogy, systematic evaluation, and continuous refinement that balance innovation with pragmatic implementation realities.